2018
DOI: 10.1002/ptr.6180
|View full text |Cite
|
Sign up to set email alerts
|

Millepachine showed novel antitumor effects in cisplatin‐resistant human ovarian cancer through inhibiting drug efflux function of ATP‐binding cassette transporters

Abstract: Millepachine (MIL), a bioactive natural chalcone from Chinese herbal medicine Millettia pachycarpa Benth, exhibits strong antitumor effects against many human cancer cells both in vitro and in vivo. In this study, we found that MIL significantly inhibited the proliferation of cisplatin-resistant A2780CP cells via inducing obvious G2/M arrest and apoptosis and down-regulating the activity of topoisomerase II protein. We further found that the mechanism by which MIL showed good antitumor effects in cisplatin-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Furthermore, it has been shown that also flavokawain A downregulated p-glycoprotein (MDR1/ABCB1) expression via inhibition of the PI3K/Akt signaling pathway in paclitaxel (PTX)-resistant lung cancer cells in a dose- and time-dependent manner [ 235 ]. The ABC protein family also includes MRP1 (ABCC1) and MRP2 (ABCC2) proteins, the level of which was statistically significantly downregulated by millepachine in cisplatin-resistant human ovarian cancer cells, known for the upregulation of these proteins [ 132 ].…”
Section: Modulation Of Other Molecular Targetsmentioning
confidence: 99%
“…Furthermore, it has been shown that also flavokawain A downregulated p-glycoprotein (MDR1/ABCB1) expression via inhibition of the PI3K/Akt signaling pathway in paclitaxel (PTX)-resistant lung cancer cells in a dose- and time-dependent manner [ 235 ]. The ABC protein family also includes MRP1 (ABCC1) and MRP2 (ABCC2) proteins, the level of which was statistically significantly downregulated by millepachine in cisplatin-resistant human ovarian cancer cells, known for the upregulation of these proteins [ 132 ].…”
Section: Modulation Of Other Molecular Targetsmentioning
confidence: 99%
“…10–12 Millepachine (compound II ), a bioactive natural chalcone, exhibits its antitumor effects in many human cancer cells through inducing obvious G2/M arrest and apoptosis. 13 Licochalcone C (compound III ) is another phenolic chalcone derivative that induces apoptosis in human oral squamous cell carcinoma cells via the regulation of the JAK2/STAT3 signalling pathway. 14…”
Section: Introductionmentioning
confidence: 99%
“…Among the vast variety of heterocyclic compounds, O(oxygen) heterocycles have attracted significant attention owing to their second highest most contribution in terms of being structural constituents of approved pharmaceuticals from U. S. Food and Drug Administration (Delost et al, 2018). Although there are a massive number of active pharmaceutical drugs possessing oxygen‐based heterocyclic skeleton which are used for the treatment of various physiological conditions like anti‐cancer (Lang et al, 2020), anti‐viral (Wadhwa et al, 2018), anti‐inflammation (Sharma et al, 2020), anti‐oxidant (Kashid et al, 2020), anti‐microbial (Desai et al, 2016), and many more yet we present here a few examples: ditazole (Mussoni et al, 1978) as an analgesic, anti‐pyretic as well as an inhibitor of platelet aggregation; bredon (Ceyhan & Karakurt, 2002) as an anti‐inflammatory and cough suppressant drug; puerarin (Zhou et al, 2014) as an anti‐cancer, anti‐oxidant and for preventing alcohol abuse; ramelteon (Simpson & Curran, 2008) for the treatment of insomnia; Millepachine (Wu et al, 2018) as an anti‐tumor agent; pyrazofurin (Canonico et al, 1982) as an anti‐viral and anti‐biotic drug; novobiocin (Mullins & Macek, 1960) as an anti‐bacterial agent and Azomycin (Nakamura, 1955) as an anti‐biotic agent (Figure 1).…”
Section: Introductionmentioning
confidence: 99%